Extensive Abdominal Electric Burn Injury - Dr. S.S. Minhas; Dr. J.K. Mahajan; Dr. D.C. Merwaha (Indian Journal of Plastic Surgery, 1991)
A rare case of electric burns of the abdominal wall resulting into damage of liver, stomach, transverse colon is presented.